1996
DOI: 10.1097/00004694-199609000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Cruciate Ligament Injuries in Skeletally Immature Patients

Abstract: Twenty-eight consecutive, skeletally immature patients (9.9-15.0 years of age at the time of injury) with total rupture of the anterior cruciate ligament (ACL) were followed up for 3-5 years. The aims of the study were to monitor the natural course of conservative treatment, to identify variables relevant to failure of conservative treatment, and to evaluate an over-the-top procedure for ACL reconstruction by using the semitendinosus tendon and avoiding the physes. The patients were interviewed according to Ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
89
0
15

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(110 citation statements)
references
References 22 publications
6
89
0
15
Order By: Relevance
“…Our median Lysholm score of 88 points is equivalent to Janarv et al [26] who reported average 87 points on the Lysholm score. A high proportion of non-operated subjects (65%) had resumed their preinjury activity level, indicating that most children had confidence in their knee function and were able to participate in free and regular activities.…”
Section: Discussiosupporting
confidence: 64%
See 2 more Smart Citations
“…Our median Lysholm score of 88 points is equivalent to Janarv et al [26] who reported average 87 points on the Lysholm score. A high proportion of non-operated subjects (65%) had resumed their preinjury activity level, indicating that most children had confidence in their knee function and were able to participate in free and regular activities.…”
Section: Discussiosupporting
confidence: 64%
“…In the present study the percentage of children who resumed pre-injury activity level was lower among children who originally participated in level 1 activities, than those who participated in level 2 activities. The variability in return to sport rates among non-operated ACL injured children is high [26,36]. Janarv et al [26] from Sweden reported that 88% of their non-operated children were performing activities at their desired activity level, McCarrol et al [36] described that 42% attempted to return to sport after conservative treatment (all failed), while no children in Woods & O'Connors [52] study continued at their pre-injury activity level, due to the restrictions in their treatment algorithm.…”
Section: Discussiomentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, bracing, activity modification, and physical therapy were used with satisfactory short term results [32][33][34]. However, more recent reports of increased risk of subsequent surgery for meniscal and chondral pathology has shifted this paradigm [34][35][36]. Still more studies have shown that nonoperative treatment of ACL injuries can lead to chronic instability and poor outcomes, with fewer athletes able to return to their sport at the same or higher level than in those undergoing reconstruction [35,37].…”
Section: Nonoperativementioning
confidence: 99%
“…Many operative treatment options have been described for these fractures, including open [36,74] or arthroscopic [42,43] reduction and casting and open [36,75,76] or arthroscopic [77,78] reduction and fixation. Fixation can be performed with sutures [77][78][79][80][81], (Fig.…”
Section: Tibial Eminence Fracturementioning
confidence: 99%